Abuse of alcohol among farmers: Prevalence and associated factors. - Roberta Machado Alves (Public Library of Science (PLoS), 2021)
We sought to identify the prevalence and factors associated with alcohol abuse among farmers living in a medium-sized municipality in northeastern Brazil during 2019 and 2020. Trained interviewers applied the standardized questionnaire to 450 participants. Sociodemographic, health, income and work characteristics were investigated. The tracking of alcohol misuse was done using the CAGE questionnaire (Cut down, Annoyed by criticism, Guilty and Eye-opener), being the cut-off point ≥ 2. Poisson Regression was applied with robust estimation to verify the reasons of prevalence (RP) in bivariate and multivariate analysis. The prevalence of alcohol abuse among farmers was 32% (95% CI 27.8-36.4). Factors such as being male, having a diagnosis of mental disorder in the family, being a smoker, and using drugs were associated with the higher prevalence of the outcome. Being 60 years old or older was associated with a lower prevalence of alcohol abuse. These results indicate the need for social support to this group of workers in the context of occupational health.